Tafsir Al-Qur’an Media Daring Laman Web Tafsiralquran.Id dan Pengaruhnya Terhadap Perkembangan Tafsir di Indonesia - Harun, Amrullah; Umar, Ratnah (Program Studi Ilmu Al-Quran dan Tafsir, 2024)
Since its beginnings, the study about interpretation has contributed to the understanding of the meaning of the Qur'an, both in terms of the text and its context. In the current digital era, an study about interpretation is evolving from print into online media, and advancements in technology have brought the field of interpretation into a new era with the advancement of scientific research. The Qur'an appears to exist on web pages dispersed throughout cyberspace, leading to the study of interpretation in online media and the subsequent shift for interpretation research towards digital research. This article's main goal is to raise awareness about the theme interpretation of the Qur'an in the digital age and how it has impacted Indonesia's growth in the field of interpretation studies. There is a qualitative approach to the process. The study's findings explain how the tafsiralquran.id website is interpreted and how this has influenced the growth of interpretation research in Indonesia. Furthermore, it implies that in order to make it easier to capture the meanings of the Qur'an in all interpretation mediums, interpretation patterns should be changed from manual to digital.